(untitled) (LACCEI, 2024)
Context: The public policies that have been formulated to the development of rural areas have been ineffective, as they do not fully respond to the particular needs and dynamics that these territories have in Colombia. Consequently, the design of sectoral policies that are mainly oriented to agricultural policy in rural areas has generated a neglect of other economic sectors that can contribute to a more balanced development, such as tourism. Based on the above, the importance of diagnoses in the design of policies oriented to the territories is identified, since they provide a clear knowledge of the current conditions. Therefore, the research presents a diagnostic model for sustainable development in rural areas of Colombia. Method: A methodology consisting of five phases is applied Identification of variables, collection of information, proposed model, validation and scenario approach. Therefore, in the first phase the variables are defined based on a review of sustainable development methodologies, then in the second phase the database of information on the variables is prepared according to secondary information sources and the comparison of the variables in the Colombian context. Similarly, in the third phase the proposed model is established, consisting of four blocks: causal model, fuzzy logic, integration of the sectors, continuous simulation model and VBA model (Visual Basic for Application) to continue with the validation and approach of scenarios in the study system. Results: Five (5) variables are identified for economic development, fifteen (15) variables for social development, six (6) variables for productive development and seven (7) variables for environmental development, for a total of thirty-three (33) variables representing sustainable development. In the same way, the importance of the dimensions of sustainable development is estimated in which they obtained weights of 0.29 - 0.18 - 0.25 - 0.29 for economic, productive, environmental and social development, respectively. Likewise, the four output variables corresponding to the individual ratings of the economic, social, productive and environmental dimensions are obtained. Finally, the fifth output variable is defined which is the integral rating of Sustainable Development (CDS), being the integration of the individual ratings. Conclusions: The purpose and functionality of the methodology for diagnosing sustainable development in rural areas is fulfilled, since it qualifies individually each of the dimensions (economic, social, productive and environmental development), and integrally the sustainable development of the 98 rural municipalities of Colombia.